Pengaruh relationship marketing terhadap kepuasan konsumen - Toriman, Muhammad (JURNAL MANAJEMEN, 2016)
The purpose of this study to analyze and determine pengruh Relationship Marketing Customer Satisfaction At PT Adira Finance in Samarinda. Basic theory used marketing management using a multiple linear regression analysis with 50 samples. Based on the results of the partial test variables significantly influence the financial benefits of variable customer satisfaction PT Adira Finance Samarinda for T value> t table then Ho Ha received and refused. Thus the hypothesis states significantly influence the financial dimensions variable customer satisfaction PT Adira Finance Samarinda, acceptedBased on the partial test results variable social benefits significantly influence customer satisfaction variables PT Adira Finance Samarinda for T value> t table then Ho Ha received and refused. Thus the hypothesis states significantly influence the social dimension of the variable customer satisfaction PT Adira Finance Samarinda, accepted.Based on the results of the partial test variables significantly influence the structural benefits of variable customer satisfaction PT Adira Finance Samarinda for T value> t table then Ho Ha received and refused. Thus the hypothesis that structural dimensions influential financial benefits, social benefits and employment benefits of structural variables significantly influence customer satisfaction PT Adira Finance Samarinda, accepted.Keyword: Relationship Marketing